A Local Wisdom-Based Sustainable Palm Oil Governance Model to Enhance Community Welfare in West Pasaman Regency - Halim Tjiwdjaja; Aep Saefullah; Alifi Restu Putera (Social Science Academic, 2026)
West Pasaman Regency in West Sumatra is among Indonesia's oldest and most productive smallholder oil palm landscapes, yet its growers remain largely outside the country's formal sustainability governance architecture. This study draws on field findings from six oil palm smallholders in West Pasaman to examine how Good Management Practices (GMP), local wisdom, socio-economic conditions, environmental awareness, and certification aspirations interact at the household level, and uses these findings to design a local wisdom-based governance model for sustainable palm oil. A qualitative descriptive case-study approach was used; structured interview data were analyzed thematically and triangulated with the broader literature on Indonesian Sustainable Palm Oil (ISPO) certification, collaborative governance theory, and smallholder institutional arrangements in West Sumatra. The findings show that while smallholders have benefited substantially from palm oil cultivation in terms of household income, their understanding of GMP remains largely conceptual rather than practical because of minimal formal training, and none of the respondents hold ISPO or RSPO certification. At the same time, customary practices such as the prohibition on land-burning, mutual-aid labor (gotong royong), and adat-based conflict resolution remain active and are perceived by farmers as more legitimate than formal regulation alone. Building on these findings and on collaborative governance theory, this study proposes a six-actor, three-pillar governance model, termed Local Wisdom-Based Sustainable Palm Oil Governance (LW-SPOG), that positions customary institutions as co-equal governance actors alongside farmers, cooperatives, partner mills, local government, and environmental NGOs. The model offers a contextually grounded complement to technocratic certification schemes and provides a practical reference for policymakers, cooperatives, and companies seeking to reconcile productivity, environmental stewardship, and cultural legitimacy in Indonesia's smallholder palm oil sector